Is Computer Assisted Language Learning Effective in Improving Learning Vocabulary among Iranian EFL Students? - Janfaza, Abusaied; Rezaei, Yousof; Soori, Afshin (JOURNAL OF ADVANCES IN LINGUISTICS, 2014)
The current study tried to investigate the impacts of using Computer Assisted Language Learning (CALL) on the development of vocabulary in comparison to the traditional method of vocabulary instruction by using the printed text materials among Iranian EFL students in a language institute in Jiroft, Iran. To conduct the study, 40 students were selected. Thus, the students were randomly divided into two equal groups of 20 students in each group, an experimental and a control group. A pre-test which was a vocabulary test was administered to all participants. The results of t-test revealed that there was no significant difference between in terms of vocabulary knowledge. The students in the experimental group had 12 sessions of instruction. They used CALL. The control group had the same hours of instruction, but the instruction was on paper and they didn't receive any audio-visual features. The result of paired sample t-test between pre-test and post-test indicated that there was a significant difference between the performance of the experimental and control groups in vocabulary knowledge. The vocabulary knowledge of the participants improved through CALL instruction.